Manual Material Handling Risk Assessment Using the Leitmerkmal Method on Porters at the Gorontalo Logistics Agency Warehouse - Siti Deafni Hadju; Herlina Jusuf; Moh Rivai Nakoe (International Journal of Health and Pharmaceutical (IJHP), 2026)
Manual material handling (MMH) activities in the warehousing sector still have the potential to cause ergonomic risks due to heavy lifting, high work frequency, and less ergonomic work postures. This study aims to analyze the level of MMH risk in porters at the Perum BULOG Gorontalo Warehouse using the Leitmerkmal Method (LMM). The study used a quantitative approach with a descriptive design. The study population consisted of 23 porters and all were sampled using a total sampling technique. Data were collected through observation, interviews, and LMM checklists, then analyzed univariately based on the assessment of work time indicators, load mass, body posture, work conditions, and the final LMM score. The results showed that all respondents had a load rating >40 kg, most had a time rating of 1 to <4 km per day, work postures were dominated by slightly bent, work conditions were classified as ergonomic, and all respondents were in the very high risk category. The conclusion of the study shows that the risk of MMH in warehouse porters at Perum BULOG Gorontalo is at a very high level which is mainly influenced by lifting loads, working time, and body posture, so that the implementation of ergonomic control is needed to reduce the risk of musculoskeletal disorders.